Female Characters and Suffering from Sexual Violence in Saowari’s Literary Works - Homchuen, Supalak; Sunthornparasathit, Nandawan (Journal of Letters, 2021)
This article aims to study the sexual violence inflicted on female characters in Saowari’s works, both in terms of the impact on the characters and criticizing social myths. The result shows that the significant effect on female characters is suffering haunting of the past. Moreover, such psychological effects resulted in the female characters losing their sense of mother. In addition, society is traumatizing the female characters who are sexually abused, by using the value of a good woman, a pure woman, to judge and evaluate them. While justice from men’s view treats victim’s body as tangible evidence without any emotional dimension, thus, the demanding justice becomes inflicting pain on women. For criticizing the social myths, Saowari’s uses literary elements as an important tool, namely victim-criminal characters and time and place which are different from the stereotype of sexual violent event in the society.